Surgical correction in an adolescent with hereditary gingival hyperplasia - Maritza Peña Sisto; Rafael Alberto Clavería Clark (Centro Provincial de Información de Ciencias Médicas, 2018)
The case report of an adolescent that was assisted in the Periodontics Service of "Dr. Juan Bruno Zayas Alfonso"TeachingGeneralHospitalinSantiago de Cubais described. He presented enlargement of the gums for more than a year, which made mastication of foods difficult and therefore, transitory digestive dysfunctions took place, besides affecting her aesthetics.  After the physical and complementary tests, the presumptive diagnosis of hereditary or family gingival hyperplasia was established and the treatment was indicated into 3 phases: initial phase, surgical corrective phase and that of periodontal support.  In the surgical phase a tissue sample was taken which pathologic analysis confirmed the initial presumptive diagnosis.